The Belt and Road Initiative and Higher Education - Li , Aisi; Ruby, Alan (International Higher Education, 2020)
China’s Belt and Road Initiative has already spawned three university alliances, but little has been investigated about their forming new higher education spaces. These three university alliances include members from within and beyond the Belt and Road. They can be interpreted as China’s rising leadership in internationalization of higher education; however, they also appear to help institutions that are usually marginalized in internationalization to gain more visibility both domestically and internationally.